Analisis Pelaksanaan Administrasi Pelayanan di Bidang Penanaman Modal pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - Tarmiji Hamid Siregar (VISA: Journal of Vision and Ideas, 2022)
This study aims to describe and analyze the implementation of service administration in the investment sector at the Medan City Investment and One Stop Integrated Service Office. In this study to collect data the author uses library research methods (Library Research). This technique aims to strengthen the facts in comparing the differences or similarities between theory and practice that the author is researching on the problem related to "Analyzing the implementation of Service Administration in the Investment Sector at the Medan City Investment and One-Stop Integrated Service Office". The results of the analysis of the implementation of service administration in the investment sector at the Medan City DPMPTSP have not been maximized and need improvement, seen from the efforts to improve the quality of services regarding ease of access which are still not maximized due to lack of socialization to the community, and the punctuality of completing the permit issuance. Suggestions from this research are to further improve the quality of service in terms of timely completion of permits and the performance of all employees in providing services to the community Keywords: Quality, Service, Licensing